A species checklist of the millipedes (Myriapoda, Diplopoda) of India - Golovatch, Sergei I.; Wesener, Thomas (Zootaxa, 2016)
At present, the millipede fauna of India comprises over 270 nominate species or subspecies in at least 90 genera, 25 families and 11 orders. As complete a catalogue as possible is compiled of all species or subspecies of Diplopoda formally reported from India, some of which remain dubious. Additionally, a checklist is also compiled of millipedes that have erroneously been recorded in India. Given also several literature lacunae, as well as numerous taxonomic problems, the number of species and even genera cannot be claimed precise. The following new transfers are proposed: Delarthrum pumilum (Attems, 1944), comb. n. ex Dasypharkis Attems, 1936; Stemmiulus crassipes (Carl, 1941), S. insolitus (Carl, 1941), S. mulierosus (Carl, 1937), S. plumipes (Carl, 1941) and S. vagans (Carl, 1941), all comb. n. ex Diopsiulus Silvestri, 1897; Cryptocorypha riparia (Carl, 1932), comb. n. ex Archandrodesmus Carl, 1932. A new record of Stenobolus insularis Carl, 1918 is given from India.